The Effect of Spiritual Leadership on Work Resilience Proactive Personality and Psychological The Mediating Role of Ownership - Afit Trisulistiono; Gede Ariadi (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Employees in Small and Medium Enterprises (SMEs) face dynamic workplace challenges that require high levels of resilience; however, the mechanisms through which leadership influences this capacity remain underexplored, particularly in traditional market settings. Objective: This study examines the mediating roles of proactive personality and psychological ownership in the relationship between spiritual leadership and work resilience, grounded in Self-Determination Theory (SDT). Methods: Using a survey design, data were collected from 189 employees working in SMEs at Banyuasri Traditional Market, Bali, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3. Results: Spiritual leadership had no direct effect on work resilience (H1 rejected, β = 0.093, p > 0.05); however, it significantly influenced psychological ownership (β = 0.493, p < 0.01) and proactive personality (β = 0.584, p < 0.01). Both mediators positively predicted work resilience. Full mediation was confirmed, with psychological ownership emerging as the dominant mediator (β = 0.264, p < 0.01) compared with proactive personality (β = 0.171, p < 0.05). Conclusion: SME leaders should prioritize cultivating psychological ownership and proactive employee behavior, as these internal psychological mechanisms are the primary pathways through which spiritual leadership strengthens work resilience.